2015
DOI: 10.1074/jbc.m115.663088
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Quality Control of Adiponectin Assembly by Endoplasmic Reticulum Chaperone ERp44

Abstract: Background: ERp44 tightly controls adiponectin assembly in the early secretory compartment. Results: ERp44 exclusively recognizes and converts assembly-trapped adiponectin intermediates back to precursors of the biologically potent high molecular weight form. Conclusion: ERp44 enhances the population of adiponectin intermediates with appropriate oxidative state for HMW assembly. Significance: Our findings provide a mechanism for the regulation of adiponectin assembly and shed light on ERp44 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…It is dormant in the ER but active in more distal compartments where it binds to its client proteins, releasing them only when their maturation is complete. Among the proteins falling into ERp44 quality control are multimeric proteins, such as immunoglobin M (IgM) and adiponectin [78][79][80]. Increased ERp44 expression may be a consequence of high demand in folding of specific proteins or triggered by other stimuli, such as redox status imbalance provoked by 17β-HSD12 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…It is dormant in the ER but active in more distal compartments where it binds to its client proteins, releasing them only when their maturation is complete. Among the proteins falling into ERp44 quality control are multimeric proteins, such as immunoglobin M (IgM) and adiponectin [78][79][80]. Increased ERp44 expression may be a consequence of high demand in folding of specific proteins or triggered by other stimuli, such as redox status imbalance provoked by 17β-HSD12 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that PDILT, together with the testis-specific CRT-like protein calsperin, is involved in the S-S bond formation and maturation of a membrane-bound metalloprotease ADAM3, which is required for sperm migration ( 46 ). ERp44 (PDIA10), a PDI protein in secretory cells, plays a regulatory role in the assembly of IgM and adiponectin in the early secretory pathway ( 47 , 48 ). ERp44 is a special member of PDI family since its activity is regulated by pH change which occurs when it shuttles between the ER and cis-Golgi compartment.…”
Section: Biological Functions Of Pdi Proteinsmentioning
confidence: 99%
“…From the NH 2 -to COOH-terminus, the primary sequence of adiponectin consists of a signal peptide, a variable region, a collagen-like domain and a globular domain. Adiponectin is extensively modified during the process of oligomeric assembly: The cysteine (C) 36 residue forms intra-and inter-trimer disulfide bridges, depicted as "S-S" [76]; The tryptophan (W) 39 residue modulates the interactions with ERp44 and the oxidative folding of trimers and hexamers [85]; A number of proline (P) and lysine (K) residues located within the collagen-like domain are post-translationally modified by hydroxylation [88 -90]; Glycosylation of the hydroxylated lysines plays a crucial role in the formation of adiponectin HMW oligomers [6,89]; A number of endoplasmic reticulum (ER) chaperones are responsible for the reduction of fully oxidized trimers and hexamers for HMW assembly [86]. Once released into the blood, the trimers, hexamers and HMW adiponectin oligomers do not spontaneously interconvert and exhibit non-overlapping biological activities by targeting distinct receptors and signaling pathways [73, 76, 78, 80, 91 -97].…”
Section: Stuctural Polymorphism Of Oligomeric Adiponectinmentioning
confidence: 99%